THE RELATIONSHIP BETWEEN THE HISTORY OF FEBRILE SEIZURE AND ATTENTION DEFICIT HYPERACTIVITY DISORDER IN CHILDREN IN MAKASSAR - RAHIMA, ANNI (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2026)
Background: Febrile seizures are convulsive episodes occurring when body temperature exceeds 38°C due to extracranial causes. Recurrent febrile seizures, particularly those lasting more than 15 minutes, may lead to neuronal damage and potentially affect cognitive development, including attention deficits and hyperactivity. Objective: This study aimed to determine the association between a history of febrile seizures and Attention Deficit/Hyperactivity Disorder (ADHD) in children. Methods: This analytic descriptive study used a cross-sectional design. The sample consisted of 32 children diagnosed with ADHD who met the inclusion criteria. Primary data were collected through structured questionnaires completed by parents or guardians. Data were analyzed using univariate and bivariate methods, with the Chi-square test used to assess statistical associations. Results: No significant association was found between a history of febrile seizures and Attention-Deficit/Hyperactivity Disorder (ADHD) (p = 0.64). In contrast, age was significantly associated with ADHD (p < 0.05). Conclusion: No significant relationship was found between febrile seizure history and ADHD in children in Makassar.